An efficient reputation-based system for wireless ad hoc networks. (1st January 2014) - Peng, Gang; Chan, Sammy; Su, Xueyuan
Consider multi-path routing and forwarding scenarios in wireless ad hoc networks. Selfish and malicious nodes both might deviate from the protocol. However, their intentions and behaviours are different. To extend our previous work on generalised second price auction for stimulating selfish nodes for cooperation, we propose a reputation-based mechanism to cope with malicious behaviours. The core of our mechanism is a decentralised reputation system. Based on available evidence, each node relies on Bayesian inference to internally update its reputation beliefs that how reliable each other node is. Instead of relying on the commonly used passive overhearing technique, 'watchdog', our proposed mechanism requires each source node to actively trigger the detection process to collect evidence towards malicious behaviours. In addition, our mechanism includes a flocking algorithm to allow careful dissemination of reputation information and thus shortens the misbehaviour detection time.